2009
DOI: 10.1258/ijsa.2008.008300
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacteria in the sputum of HIV-infected patients: infection or colonization?

Abstract: It can be difficult to establish the clinical significance of the isolation of non-tuberculous mycobacteria (NTM) from the sputum of HIV-infected patients. In this observational study, we have investigated factors associated with having NTM infection. During the period of the study, 10 patients had NTM infection and 14 had NTM colonization. Factors associated with having NTM infections were: CD4 lymphocyte count <50 cells/mL (odds ratio [OR] 10; 95% confidence interval [CI] 1.4-69.3), haemoglobin <11 g/dL (OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…kansasii is considered one of the most virulent NTM, and observational studies have reported variable mortality rates. 9,10 The clinical presentation is similar to that of M. tuberculosis, [9][10][11] with symptoms of fever and cough usually lasting more than 30 days, [10][11][12][13][14] which is considerably longer than in our patient. After initiation of HAART, the deterioration in his general condition could have occurred for several reasons, one of them being IRIS.…”
Section: Discussionsupporting
confidence: 58%
“…kansasii is considered one of the most virulent NTM, and observational studies have reported variable mortality rates. 9,10 The clinical presentation is similar to that of M. tuberculosis, [9][10][11] with symptoms of fever and cough usually lasting more than 30 days, [10][11][12][13][14] which is considerably longer than in our patient. After initiation of HAART, the deterioration in his general condition could have occurred for several reasons, one of them being IRIS.…”
Section: Discussionsupporting
confidence: 58%
“…However, when it is isolated from non-sterile sites, such as the respiratory or GI tract, the diagnosis can be less definitive. A case series from Spain, conducted between 1998 and 2005, identified 26 HIV-infected patients with NTM isolates from sputum 10. As in our patient, they used clinical criteria to establish a diagnosis of colonisation versus infection; some of the factors associated with disease were CD4+ T-cell count <50/µL, weight loss, haemoglobin <11 g/dL and duration of symptoms longer than a month.…”
Section: Discussionmentioning
confidence: 99%
“…Although pooled specificity of urine LAM was relatively high (Ն96%), specificity was found to be low (84% to 94%) in several studies and even lower in studies of serum and sputum LAM. Possible reasons include the presence of latent TB infection, misclassification of subclinical TB cases, or cross-reactivity with nontuberculous mycobacteria (3,28,30,36). Studies are now required to clarify the cause of reduced LAM specificity.…”
Section: Discussionmentioning
confidence: 99%